Ano1, a Ca2+‐activated Cl− channel, coordinates contractility in mouse intestine by Ca2+ transient coordination between interstitial cells of Cajal. (20th August 2014) - Singh, Raman Deep; Gibbons, Simon J.; Saravanaperumal, Siva Arumugam; Du, Peng; Hennig, Grant W.; Eisenman, Seth T.; Mazzone, Amelia; Hayashi, Yujiro; Cao, Chike; Stoltz, Gary J.; Ordog, Tamas; Rock, Jason R.; et al.
Abstract : Key points: Ano1, a Ca 2+ ‐activated Cl − channel, is expressed in interstitial cells of Cajal (ICC) throughout the gut. We report here that it is required to maintain coordinated Ca 2+ transients within myenteric ICC of mouse small intestine. Ca 2+ transients in Ano1 WT mice were rhythmic and coordinated whereas uncoordinated Ca 2+ transients were seen in knockout mice. Ca 2+ transients were un‐coordinated following pharmacological block of Ano1 in WT mice using niflumic acid, 5‐nitro‐2‐(3‐phenylpropylamino) benzoic acid and 4, 4′‐diisothiocyanato‐2, 2′‐stilbenedisulfonic acid disodium salt. Transient knockdown of Ano1 in organotypic cultures with short hairpin RNA to Ano1 in WT tissues also caused loss of coordinated Ca 2+ transients. Contractility of Ano1 knockout mouse intestinal segments in organ bath experiments was significantly decreased, less coordinated and non‐rhythmic. Spatiotemporal maps from knockout mouse small intestine also showed loss of phasic contractile activity. This study provides important information on the basic mechanisms driving coordinated contractile activity in the gastrointestinal tract. Abstract: Interstitial cells of Cajal (ICC) are pacemaker cells that generate electrical activity to drive contractility in the gastrointestinal tract via ion channels. Ano1 ( Tmem16a ), a Ca 2+ ‐activated Cl − channel, is an ion channel expressed in ICC. Genetic deletion of Ano1 in mice resulted in loss of slow waves in smooth muscle of small intestine. In this study, we show that Ano1 is required to maintain coordinated Ca 2+ transients between myenteric ICC (ICC‐MY) of small intestine. First, we found spontaneous Ca 2+ transients in ICC‐MY in both Ano1 WT and knockout (KO) mice. However, Ca 2+ transients within the ICC‐MY network in Ano1 KO mice were uncoordinated, while ICC‐MY Ca 2+ transients in Ano1 WT mice were rhythmic and coordinated. To confirm the role of Ano1 in the loss of Ca 2+ transient coordination, we used pharmacological inhibitors of Ano1 activity and shRNA‐mediated knock down of Ano1 expression in organotypic cultures of Ano1 WT small intestine. Coordinated Ca 2+ transients became uncoordinated using both these approaches, supporting the conclusion that Ano1 is required to maintain coordination/rhythmicity of Ca 2+ transients. We next determined the effect on smooth muscle contractility using spatiotemporal maps of contractile activity in Ano1 KO and WT tissues. Significantly decreased contractility that appeared to be non‐rhythmic and uncoordinated was observed in Ano1 KO jejunum. In conclusion, Ano1 has a previously unidentified role in the regulation of coordinated gastrointestinal smooth muscle function through coordination of Ca 2+ transients in ICC‐MY.